Magnetic field of the system ``neutron star plus wormhole’’ with a dilatonic scalar field - Aringazin, A.; Dzhunushaliev, V.; Folomeev, V. (Recent Contributions to Physics, 2018)
The mixed configuration with a nontrivial spacetime topology consisting of a wormhole filled with a strongly magnetized neutron fluid is considered. The nontrivial topology is provided by a ghost scalar dilatonic field interacting nonminimally with a magnetic field. The neutron fluid is described by a realistic Sly equation of state. The magnetic field is modeled in the form of an axisymmetric poloidal magnetic field created by toroidal electric currents. The energy density of the magnetic field is assumed much to be smaller than those of scalar and gravitational fields. Comparing such mixed configurations with ordinary neutron stars, the question of the influence of the nontrivial topology and the dilatonic interaction on the structure of the interior magnetic field is studied. The radial and tangential components of the magnetic field strength are calculated. Distributions of the magnetic field equipotential lines for ordinary neutron star and the mixed system under consideration are plotted